A Novel Approach for Security in Cloud Environment - Prithika, M (International Journal of Computer Sciences and Engineering, 2025)
Cloud registering is one of the present most energizing advances, since it can lessen the expense and intricacy of uses, and it is adaptable and versatile. These advantages changed cloud registering from a marvelous thought into one of the quickest developing innovations today. As a matter of fact, virtualization technology is based on virtualization technology which is an old technology and has had security issues that must be tended to before cloud technology is influenced by them. What's more, the virtualization technology has limit security abilities so as to anchor wide zone condition, for example, the cloud. Along these lines, the improvement of a powerful security framework requires changes in conventional virtualization engineering. This paper proposes new security design in a hypervisor-based virtualization technology so as to anchor the cloud condition